Polarizing plate and image display device using the same

CN117597614BActive Publication Date: 2026-10-09SUMITOMO CHEM CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202280047146.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-07-13
Filing Date
2022-06-27
Publication Date
2026-10-09
Estimated Expiration
2042-06-27

AI Technical Summary

Technical Problem

[0008]但是,报道了在采用这样的构成的情况下,在高温环境下偏振板的透射率显著降低

Benefits of technology

[0041] According to the present invention, a polarizing plate is provided having an adhesive layer formed of an adhesive having a sufficient production life, and suppressing the decrease in transmittance when exposed to high-temperature environments. Furthermore, by using the polarizing plate of the present invention, an image display device can be provided that suppresses the decrease in transmittance even when exposed to high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004642170240000271
    Figure BDA0004642170240000271
  • Figure BDA0004642170240000301
    Figure BDA0004642170240000301
Patent Text Reader

Abstract

The present invention provides a polarizing plate having an adhesive layer formed of an adhesive having a sufficiently long pot life for production, and a reduction in transmittance when exposed to a high-temperature environment is suppressed. The present invention provides a polarizing plate having a polarizing element in which a dichroic dye is adsorbed and oriented in a polyvinyl alcohol-based resin layer, and a transparent protective film laminated to at least one face of the polarizing element, the polarizing element and the transparent protective film being bonded by an adhesive layer formed of an adhesive containing a first compound, a second compound, and a third compound, the first compound being at least one selected from the group consisting of urea, a urea derivative, thiourea, and a thiourea derivative, the second compound being a dialdehyde, and the third compound being a dicarboxylic acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to polarizing plates and image display devices. Background Technology

[0002] Liquid crystal displays (LCDs) are not only used in LCD televisions, but also widely used in personal computers, mobile devices such as mobile phones, and automotive applications such as car navigation systems. Typically, an LCD has a liquid crystal panel with polarizing plates bonded to both sides of the liquid crystal cells using adhesive. The display is achieved by controlling the light from the backlight using the liquid crystal panel. In recent years, organic EL displays have also been widely used, similarly to LCDs, in televisions, mobile devices such as mobile phones, and automotive applications such as car navigation systems. In organic EL displays, to suppress the reflection of external light by the metal electrodes (cathodes) and thus prevent it from appearing as a mirror, a circular polarizing plate (a laminate containing polarizing elements and a λ / 4 plate) is sometimes placed on the viewing side surface of the image display panel.

[0003] In polarizing plates, polyvinyl alcohol (PVA) resin adhesives are used to achieve good adhesion when bonding polarizing elements to a protective film. However, Patent Document 1 (Japanese Patent Application Publication No. 2005-189615) points out that PVA resin adhesives cannot achieve a sufficient pot life. "Insufficient pot life" refers to a short service life of the adhesive. Patent Document 2 (Japanese Patent Application Publication No. 2010-276673) describes a method to achieve a sufficient pot life for production by adding maleic acid along with a crosslinking agent to the adhesive.

[0004] As mentioned above, polarizing plates are increasingly being used in automobiles as components of image display devices such as liquid crystal displays and organic EL displays. Compared to those used in mobile applications such as televisions and mobile phones, polarizing plates used in automotive image display devices are mostly exposed to high-temperature environments, thus requiring minimal changes in characteristics at higher temperatures (high-temperature durability).

[0005] On the other hand, to prevent damage to the image display panel from impacts from external surfaces, there is an increasing trend of installing a front panel (also known as a "window layer") made of transparent resin or glass at a position closer to the viewing side than the image display panel. In image display devices equipped with touch panels, a configuration is widely adopted where the touch panel is positioned further to the viewing side than the image display panel, and a front panel is positioned further to the viewing side than the touch panel.

[0006] In such a configuration, if an air layer exists between the image display panel and transparent components such as the front panel and touch panel, glare from reflected external light caused by light reflection at the air layer interface will occur, leading to a decrease in image visibility. Therefore, a trend is emerging where the space between the polarizer disposed on the viewing side surface of the image display panel and the transparent components is filled with a layer other than the air layer, typically a solid layer (hereinafter sometimes referred to as "interlayer filler"). The interlayer filler is preferably a material with a refractive index close to that of the polarizer or the transparent components. As the interlayer filler, adhesives or UV-curable adhesives can be used to suppress the decrease in visibility caused by reflection at the interface and to bond and fix the components together (for example, see Japanese Patent Application Publication No. 11-174417 (Patent Document 3)).

[0007] Interlayer filling is widely used in mobile applications such as mobile phones that are frequently used outdoors. In addition, due to the increasing demand for visibility in recent years, interlayer filling structures have also been studied in in-vehicle applications such as car navigation devices, which involve placing a front transparent panel on the surface of the image display panel and filling the gap between the panel and the front transparent panel with an adhesive layer.

[0008] However, it has been reported that with such a configuration, the transmittance of the polarizing plate decreases significantly under high-temperature conditions. In Japanese Patent Application Publication No. 2014-102353 (Patent Document 4), a solution to this problem is proposed: a method to suppress the decrease in transmittance by setting the water content per unit area of ​​the polarizing plate to a predetermined amount or less, and setting the saturated water absorption of the transparent protective film adjacent to the polarizing element to a predetermined amount or less.

[0009] Existing technical documents

[0010] Patent documents

[0011] Patent Document 1: Japanese Patent Application Publication No. 2005-189615

[0012] Patent Document 2: Japanese Patent Application Publication No. 2010-276673

[0013] Patent Document 3: Japanese Patent Application Publication No. 11-174417

[0014] Patent Document 4: Japanese Patent Application Publication No. 2014-102353 Summary of the Invention

[0015] The problem that the invention aims to solve

[0016] The object of the present invention is to provide a new polarizing plate having an adhesive layer formed of an adhesive having a sufficient production life and suppressing the decrease in transmittance when exposed to a high temperature environment, an image display device using the polarizing plate, and an adhesive.

[0017] Methods for solving problems

[0018] The present invention provides a polarizing plate and an image display device, as illustrated below.

[0019] [1] A polarizing plate having a polarizing element and a transparent protective film, wherein the polarizing element is formed by adsorbing and oriented dichroic pigments on a polyvinyl alcohol-based resin layer, and the transparent protective film is laminated on at least one side of the polarizing element.

[0020] The aforementioned polarizing element and the aforementioned transparent protective film are bonded together by an adhesive layer formed from an adhesive containing the first compound, the second compound, and the third compound.

[0021] The first compound mentioned above is selected from at least one of urea, urea derivatives, thiourea, and thiourea derivatives.

[0022] The second compound mentioned above is a dialdehyde.

[0023] The third compound mentioned above is a dicarboxylic acid.

[0024] [2] According to the polarizing plate described in [1], wherein the adhesive comprises a polyvinyl alcohol resin.

[0025] [3] According to the polarizing plate described in [2], in the adhesive, the content of the third compound is 0.01 parts by mass or more and 400 parts by mass or less relative to 100 parts by mass of the polyvinyl alcohol resin.

[0026] [4] According to the polarizing plate described in [2] or [3], wherein, in the adhesive, the content of the first compound is 0.1 parts by mass or more and 400 parts by mass or less relative to 100 parts by mass of the polyvinyl alcohol resin.

[0027] [5] The polarizing plate according to any one of [2] to [4], wherein, in the adhesive, the content of the second compound is 0.03 parts by mass or more and 20 parts by mass or less relative to 1 part by mass of the first compound.

[0028] [6] The polarizing plate described in any one of [1] to [5], wherein the dialdehyde is glyoxal.

[0029] [7] The polarizing plate according to any one of [1] to [6], wherein the thickness of the adhesive layer is 0.01 μm or more and 7 μm or less.

[0030] [8] A polarizing plate according to any one of [1] to [7], wherein the polarizing plate is used in an image display device.

[0031] In the above-mentioned image display device, a solid layer is provided in contact with both sides of the polarizing plate.

[0032] [9] An image display device having an image display unit, a first adhesive layer laminated on the observation side surface of the image display unit, and a polarizing plate described in any one of [1] to [8] laminated on the observation side surface of the first adhesive layer.

[0033]

[10] The image display device described in [9] further comprises a second adhesive layer laminated on the observation side surface of the polarizing plate and a transparent component laminated on the observation side surface of the second adhesive layer.

[0034]

[11] According to the image display device described in

[10] , the transparent component is a glass plate or a transparent resin plate.

[0035]

[12] According to the image display device described in

[10] , the transparent component is a touch panel.

[0036]

[13] An adhesive comprising a first compound, a second compound, and a third compound,

[0037] The first compound mentioned above is selected from at least one of urea, urea derivatives, thiourea, and thiourea derivatives.

[0038] The second compound mentioned above is a dialdehyde.

[0039] The third compound mentioned above is a dicarboxylic acid.

[0040] Invention Effects

[0041] According to the present invention, a polarizing plate is provided having an adhesive layer formed of an adhesive having a sufficient production life, and suppressing the decrease in transmittance when exposed to high-temperature environments. Furthermore, by using the polarizing plate of the present invention, an image display device can be provided that suppresses the decrease in transmittance even when exposed to high-temperature environments. Detailed Implementation

[0042] The embodiments of the present invention will be described below, but the present invention is not limited to the following embodiments.

[0043] [Polarizing plate]

[0044] The polarizing plate of an embodiment of the present invention has a polarizing element and a transparent protective film. The polarizing element is formed by adsorbing and oriented a dichroic pigment onto a layer containing a polyvinyl alcohol-based resin. The polarizing element and the transparent protective film are bonded together by an adhesive layer formed of an adhesive containing a first compound, a second compound, and a third compound.

[0045] The first compound is selected from at least one of urea, urea derivatives, thiourea, and thiourea derivatives. The second compound is a dialdehyde. The third compound is a dicarboxylic acid.

[0046] As for conventional polarizing plates with excellent high-temperature durability, it is known that, for example, when the polarizing plate is used alone, it can suppress the decrease in transmittance even after being placed in an environment of 95°C for 1000 hours. However, even with such polarizing plates, when used in interlayer filling structures, a significant decrease in transmittance is sometimes observed in the central part of the polarizing plate surface when placed in an environment of 105°C. It is believed that the significant decrease in transmittance of polarizing plates in high-temperature environments is a problem that is particularly prone to occur when image display devices using interlayer filling structures, in which one side of the polarizing plate is bonded to the image display unit and the other side is bonded to transparent components such as the touch panel and front panel, are exposed to high-temperature environments.

[0047] A polarizing plate with significantly reduced transmittance in its interlayer filling configuration showed reduced transmittance at 1100 cm⁻¹ in Raman spectroscopy. -1 Nearby (from the =CC= key) and 1500cm -1 The presence of peaks near the -C=C- bond suggests the formation of a polyene structure (-C=C). n - It is speculated that the polyene structure is produced by polyene formation of polyvinyl alcohol constituting the polarization element through dehydration (Patent Document 4,

[0012] paragraph).

[0048] The polarizing plate of the present invention further improves high-temperature durability. When assembled into an image display device with interlayer filling, the polarizing plate of the present invention suppresses the decrease in transmittance even when exposed to high-temperature environments, such as 105°C. This effect is presumably due to the synergistic effect of the first, second, and third compounds present in the adhesive layer, which suppresses the polyene oxidation of the polyvinyl alcohol constituting the polarizing element. This effect is not limited to cases with low moisture content of the polarizing plate; it can also be achieved when the moisture content of the polarizing plate is high.

[0049] The polarizing plate of the present invention preferably has at least one of the features described in (a) and (b).

[0050] (a) The moisture content of the polarization element is above the equilibrium moisture content at 20°C and 30% relative humidity and below the equilibrium moisture content at 20°C and 70% relative humidity.

[0051] (b) The moisture content of the polarizing plate is above the equilibrium moisture content at 20°C and 30% relative humidity and below the equilibrium moisture content at 20°C and 70% relative humidity.

[0052] <Polarization element>

[0053] As a polarizing element formed by adsorbing and oriented a dichroic dye onto a layer containing a polyvinyl alcohol (hereinafter also referred to as "PVA")-based resin (hereinafter also referred to as "PVA-based resin layer"), known polarizing elements can be used. Examples of polarizing elements include a stretched film obtained by dyeing a PVA-based resin film with a dichroic dye and then uniaxially stretching it; and a stretched layer obtained by dyeing a coating layer formed by coating a substrate film with a coating liquid containing a PVA-based resin, and then uniaxially stretching the stretched film. Stretching can be performed after dyeing with the dichroic dye, or while dyeing, or after stretching.

[0054] PVA-based resins are obtained by saponifying polyvinyl acetate-based resins. Besides polyvinyl acetate as a homopolymer of vinyl acetate, copolymers of vinyl acetate and other monomers that can be copolymerized with it can also be cited as polyvinyl acetate-based resins. Examples of other monomers that can be copolymerized include unsaturated carboxylic acids, olefins such as ethylene, vinyl ethers, and unsaturated sulfonic acids.

[0055] The PVA-based resin layer is preferably formed from a PVA-based resin with a boron adsorption rate of 5.70% by mass or more. That is, the boron adsorption rate of the PVA-based resin in the raw material stage before dyeing and stretching is 5.70% by mass or more. By using such a PVA-based resin, the transmittance is less likely to decrease, even when exposed to a high-temperature environment of 105°C. Furthermore, the boron adsorption rate of the PVA-based resin is preferably 10% by mass or less. By using such a PVA-based resin to manufacture polarizing elements, the boric acid concentration in the boric acid treatment bath is not high, the boric acid treatment time is shortened, the desired polarizing element is easily obtained, and the productivity of polarizing elements is improved. If the boron adsorption rate of the PVA-based resin is 10% by mass or less, boron enters the PVA-based resin layer in an appropriate amount, easily reducing the shrinkage force of the polarizing element. As a result, when assembled into an image display device, defects such as peeling between the front panel and other components and the polarizing plate are less likely to occur. The boron adsorption rate of the PVA-based resin can be measured using the method described in the examples below.

[0056] The boron adsorption rate of PVA-based resins reflects the spacing between molecular chains and the characteristics of the crystal structure. It is believed that PVA-based resins with a boron adsorption rate of 5.70% by mass or higher have wider molecular chain spacing and fewer crystals compared to those with a boron adsorption rate of less than 5.70% by mass. Therefore, it is speculated that boron, the first metal ion, and the second metal ion can easily enter the PVA-based resin layer, thus better preventing polyolefin formation under high-temperature environments.

[0057] The boron adsorption rate of PVA-based resins can be adjusted, for example, by pretreatment of the PVA-based resins before manufacturing polarizing elements, such as hot water treatment, acidic solution treatment, ultrasonic irradiation treatment, or radiation irradiation treatment. These treatments can increase the spacing between the molecular chains in the PVA-based resin or disrupt the crystal structure. Examples of hot water treatment include immersion in pure water at 30°C to 100°C for 1 to 90 seconds followed by drying. Examples of acidic solution treatment include immersion in an aqueous solution of boric acid with a concentration of 10% to 20% by mass for 1 to 90 seconds followed by drying. Examples of ultrasonic treatment include irradiation with ultrasound at a frequency of 20 to 29 kC at an output power of 200 W to 500 W for 30 seconds to 10 minutes. Ultrasonic treatment can be performed in solvents such as water.

[0058] The degree of saponification of the PVA-based resin is preferably 85 mol% or more, more preferably 90 mol% or more, and even more preferably 99 mol% or more and 100 mol% or less. The degree of polymerization of the PVA-based resin is, for example, 1000 or more and 10000 or less, preferably 1500 or more and 5000 or less. The PVA-based resin can be modified, for example, it can be aldehyde-modified polyvinyl formal, polyvinyl acetal, polyvinyl butyral, etc.

[0059] The thickness of the polarizing element is preferably 3 μm or more and 35 μm or less, more preferably 4 μm or more and 30 μm or less, and even more preferably 5 μm or more and 25 μm or less. By making the thickness of the polarizing element 35 μm or less, the effect of polyolefination of PVA-based resin on the reduction of optical properties under high-temperature conditions can be suppressed. By making the thickness of the polarizing element 3 μm or more, it is easy to manufacture a configuration that achieves the desired optical properties.

[0060] The polarizing element preferably comprises a first compound, a second compound, and a third compound. In this embodiment, since the polarizing element and the transparent protective film are bonded together by an adhesive layer formed from an adhesive containing the first, second, and third compounds, it is presumed that a portion of the first compound, a portion of the second compound, and a portion of the third compound transferred from the adhesive layer are included in the polarizing element. The first, second, and third compounds in the polarizing element may include compounds added during the manufacturing process of the polarizing element. By having an adhesive layer containing the first, second, and third compounds, the transmittance is less likely to decrease even when the polarizing plate is exposed to a high-temperature environment. Furthermore, by having an adhesive layer containing the first, second, and third compounds, the decrease in polarization degree can be suppressed even when the polarizing plate is exposed to a high-temperature environment. When two polarizers are configured in an orthogonal Nicol relationship, light leakage (hereinafter also referred to as "orthogonal light leakage") is likely to occur if the polarization degree of the polarizers decreases. However, according to the present invention, the polarization degree does not easily decrease even when exposed to high temperature environments, and therefore orthogonal light leakage is easily suppressed. It is presumed that this is because the polyolefination of the PVA-based resin is suppressed by the synergistic effect of the first, second, and third compounds contained in the polarizing element.

[0061] In manufacturing polarizing elements, methods containing the first, second, and third compounds include impregnating a PVA-based resin layer in a processing solvent containing the first and / or second and / or third compounds, or spraying, dripping, or adding the processing solvent to the PVA-based resin layer. Preferably, the method involves impregnating the PVA-based resin layer in a processing solvent containing all of the first, second, and third compounds. Specific examples of the first, second, and third compounds include compounds exemplified as compounds contained in the adhesives described later.

[0062] The process of immersing the PVA-based resin layer in a treatment solvent containing the first, second, and third compounds can be performed simultaneously with the swelling, stretching, dyeing, crosslinking, and cleaning processes described later in the polarization element manufacturing method, or it can be performed separately from these processes. The process of incorporating the first, second, and third compounds into the PVA-based resin layer is preferably performed after dyeing the PVA-based resin layer with iodine, and more preferably simultaneously with the crosslinking process after dyeing. According to this method, the color variation is small, and the impact on the optical properties of the polarization element can be reduced.

[0063] To make the polarizing element contain the first compound, the second compound, and the third compound, both addition during the manufacturing of the polarizing element and addition to the adhesive can be performed. For example, an adhesive containing the first compound, the second compound, and the third compound can be used as an adhesive, and at least one of the first compound, the second compound, and the third compound can also be added during the manufacturing of the polarizing element.

[0064] (Compound 1)

[0065] The first compound is selected from at least one of urea, urea derivatives, thiourea, and thiourea derivatives. One first compound may be used alone or in combination of two or more. The first compound may include water-soluble and water-poorly soluble compounds; any one of the first compounds may be used. When using a water-poorly soluble first compound in a water-soluble adhesive, it is preferable to design a dispersion method that does not cause an increase in haze or the like after the adhesive layer is formed.

[0066] (Urea derivatives)

[0067] Urea derivatives are compounds in which at least one of the four hydrogen atoms of a urea molecule has been substituted with a substituent. In this case, there are no particular limitations on the substituent, but substituents containing carbon, hydrogen, and oxygen atoms are preferred.

[0068] Specific examples of urea derivatives, as 1-substituted ureas, include methylurea, ethylurea, propylurea, butylurea, isobutylurea, N-octadecylurea, 2-hydroxyethylurea, hydroxyurea, acetylurea, allylurea, 2-propynylurea, cyclohexylurea, phenylurea, 3-hydroxyphenylurea, (4-methoxyphenyl)urea, benzylurea, benzoylurea, o-tolylurea, and p-tolylurea.

[0069] Examples of disubstituted ureas include 1,1-dimethylurea, 1,3-dimethylurea, 1,1-diethylurea, 1,3-diethylurea, 1,3-di(hydroxymethyl)urea, 1,3-tert-butylurea, 1,3-dicyclohexylurea, 1,3-diphenylurea, 1,3-di(4-methoxyphenyl)urea, 1-acetyl-3-methylurea, 2-imidazolidineone (vinylurea), and tetrahydro-2-pyrimidinone (acrylurea).

[0070] Examples of 4-substituted ureas include tetramethylurea, 1,1,3,3-tetraethylurea, 1,1,3,3-tetrabutylurea, 1,3-dimethoxy-1,3-dimethylurea, 1,3-dimethyl-2-imidazolidineone, and 1,3-dimethyl-3,4,5,6-tetrahydro-2(1H)-pyrimidinone.

[0071] (Thiocarbamide derivatives)

[0072] Thiourea derivatives are compounds in which at least one of the four hydrogen atoms of a thiourea molecule is substituted with a substituent. In this case, there are no particular restrictions on the substituent, but substituents containing carbon, hydrogen, and oxygen atoms are preferred.

[0073] Specific examples of thiourea derivatives, as 1-substituted thioureas, include N-methylthiourea, ethylthiourea, propylthiourea, isopropylthiourea, 1-butylthiourea, cyclohexylthiourea, N-acetylthiourea, N-allylthiourea, (2-methoxyethyl)thiourea, N-phenylthiourea, (4-methoxyphenyl)thiourea, N-(2-methoxyphenyl)thiourea, N-(1-naphthyl)thiourea, (2-pyridyl)thiourea, o-tolylthiourea, and p-tolylthiourea.

[0074] Examples of disubstituted thioureas include 1,1-dimethylthiourea, 1,3-dimethylthiourea, 1,1-diethylthiourea, 1,3-diethylthiourea, 1,3-dibutylthiourea, 1,3-diisopropylthiourea, 1,3-dicyclohexylthiourea, N,N-diphenylthiourea, N,N'-diphenylthiourea, 1,3-di(o-tolyl)thiourea, 1,3-di(p-tolyl)thiourea, 1-benzyl-3-phenylthiourea, 1-methyl-3-phenylthiourea, N-allyl-N'-(2-hydroxyethyl)thiourea, and ethylenethiourea.

[0075] Examples of 3-substituted thioureas include trimethylthiourea, and examples of 4-substituted thioureas include tetramethylthiourea and 1,1,3,3-tetraethylthiourea.

[0076] In the first compound, when used in an image display device with interlayer filling, considering the aspects of suppressing the decrease in transmittance under high-temperature environments and minimizing the decrease in polarization degree (suppressing orthogonal light leakage), urea derivatives or thiourea derivatives are preferred, and urea derivatives are more preferred. Among the urea derivatives, 1-substituted urea or 2-substituted urea are preferred, and 1-substituted urea is more preferred. Among the 2-substituted urea, there are 1,1-substituted urea and 1,3-substituted urea, and 1,3-substituted urea is more preferred.

[0077] (Compound 2)

[0078] The second compound is a dialdehyde. Examples of dialdehydes include glyoxal, malondialdehyde, and succinaldehyde. Glyoxal, which has a simple structure and is highly reactive, is particularly preferred. Hereinafter, glyoxal will sometimes be described, but as mentioned above, conventionally known dialdehydes can be used, and it is not limited to glyoxal.

[0079] (Compound 3)

[0080] The third compound is a dicarboxylic acid. Examples of dicarboxylic acids include oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, octanoic acid, azelaic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, tartaric acid, glutamic acid, malic acid, maleic acid, fumaric acid, itaconic acid, mucoaconic acid, 1,4-cyclohexanedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 4,4'-biphenyldicarboxylic acid, 2,5-pyridinedicarboxylic acid, 3,5-pyridinedicarboxylic acid, diphenylsulfonedicarboxylic acid, diphenylmethanedicarboxylic acid, oxaloacetic acid, methyl fumaric acid, and 2,6-pyridinedicarboxylic acid. Citric acid, malic acid, maleic acid, or tartaric acid are preferred. These dicarboxylic acids can be used alone or in combination of two or more.

[0081] Polarizing elements typically contain potassium ions (also referred to as "first metal ions"), and preferably also contain other metal ions besides potassium ions (also referred to as "second metal ions"). The content of the second metal ions in the polarizing element is preferably 0.05% by mass or more and 10.0% by mass or less, more preferably 0.05% by mass or more and 8.0% by mass or less, and even more preferably 0.1% by mass or more and 6.0% by mass or less. When the content of the second metal ions in the polarizing element exceeds 10.0% by mass, the degree of polarization may sometimes decrease under high temperature and high humidity conditions. Furthermore, when the content of the second metal ions is less than 0.05% by mass, the improvement in durability under high temperature conditions may sometimes be insufficient. It should be noted that the content of the second metal ions in the polarizing element can be calculated, for example, by high-frequency inductively coupled plasma (ICP) emission spectrophotometry as a mass fraction (mass%) of the metal element relative to the mass of the polarizing element. It is believed that metal elements exist in polarization elements as metal ions or as cross-linked structures formed with the constituent elements of polyvinyl alcohol resins. The content of the second metal ion mentioned here is a value based on metal atoms.

[0082] The second metal ion is not limited to any metal ion other than potassium ions, but is preferably an ion of a metal other than an alkali metal. In particular, from the viewpoint of adjusting the color tone and imparting durability, at least one metal ion from the group consisting of transition metals such as cobalt, nickel, zinc, chromium, aluminum, copper, manganese, and iron is preferred. Among these metal ions, zinc ions are preferred from the viewpoint of adjusting the color tone and imparting heat resistance.

[0083] The boron content of the polarizing element is preferably 2.4% by mass or more. Furthermore, the boron content is preferably 3.9% by mass or more and 8.0% by mass or less, more preferably 4.2% by mass or more and 7.0% by mass or less, and even more preferably 4.4% by mass or more and 6.0% by mass or less. When the boron content of the polarizing element exceeds 8.0% by mass, the shrinkage force of the polarizing element increases, sometimes resulting in defects such as peeling from the front panel or other components that are bonded to the image display device. Additionally, when the boron content is less than 2.4% by mass, the desired optical properties may not be achieved. It should be noted that the boron content in the polarizing element can be calculated, for example, by high-frequency inductively coupled plasma (ICP) emission spectrophotometry as a mass fraction (mass %) of boron relative to the mass of the polarizing element. It is assumed that boron exists in the polarizing element in the form of boric acid or a cross-linked structure formed with a component of polyvinyl alcohol resin; the boron content mentioned here is a value based on boron atoms (B).

[0084] By ensuring that the boron content of the polarization element is 2.4% by mass or more and 8.0% by mass or less, the decrease in transmittance is further suppressed even when the element, as a component of an image display device consisting of interlayer filler, is exposed to a high-temperature environment. This is presumably because, when the boron content of the polarization element is 2.4% by mass or more and 8.0% by mass or less, polyolefin formation is less likely to occur even at high temperatures, thus suppressing the decrease in transmittance.

[0085] From the viewpoint of suppressing the degradation of the optical properties of the polarization element under high-temperature conditions, the potassium ion content in the polarization element is preferably 0.28% by mass or more, more preferably 0.32% by mass or more, and even more preferably 0.34% by mass or more. Furthermore, from the viewpoint of suppressing color tone changes under high-temperature conditions, it is preferably 0.60% by mass or less, more preferably 0.55% by mass or less, and even more preferably 0.50% by mass or less. The potassium ion content can be determined using the same method as the content of the second metal ion, and the potassium ion content mentioned here is a value calculated on a potassium atomic basis.

[0086] (Manufacturing method of polarization element)

[0087] There is no particular limitation on the manufacturing method of polarization elements. A typical method is to produce them by feeding out a pre-wound PVA-based resin film and stretching, dyeing, cross-linking, etc. (hereinafter referred to as "manufacturing method 1"). Another method includes coating a coating liquid containing PVA-based resin onto a substrate film to form a PVA-based resin layer as a coating layer, and stretching the resulting laminate (hereinafter referred to as "manufacturing method 2").

[0088] Manufacturing method 1 can be carried out through the following steps: a step of uniaxially stretching a PVA-based resin film, a step of dyeing the PVA-based resin film with dichroic pigments such as iodine to adsorb the dichroic pigments, a step of treating the PVA-based resin film with adsorbed dichroic pigments with a boric acid aqueous solution, and a step of washing with water after treatment with boric acid aqueous solution.

[0089] The swelling process involves immersing a PVA-based resin film in a swelling bath. This process removes surface contaminants and sealing agents from the PVA-based resin film and also suppresses uneven dyeing by causing the film to swell. The swelling bath typically uses a water-based medium, such as water, distilled water, or pure water. Surfactants, alcohols, etc., can be added to the swelling bath using conventional methods. From the viewpoint of controlling the potassium content of the polarizing element, potassium iodide can be used in the swelling bath. In this case, the concentration of potassium iodide in the swelling bath is preferably 1.5% by mass or less, more preferably 1.0% by mass or less, and even more preferably 0.5% by mass or less.

[0090] The temperature of the swelling bath is preferably 10°C or higher and 60°C or lower, more preferably 15°C or higher and 45°C or lower, and even more preferably 18°C ​​or higher and 30°C or lower. Since the degree of swelling of the PVA resin film is affected by the temperature of the swelling bath, the immersion time in the swelling bath cannot be fixed. It is preferably 5 seconds or higher and 300 seconds or lower, more preferably 10 seconds or higher and 200 seconds or lower, and even more preferably 20 seconds or higher and 100 seconds or lower. The swelling process can be performed only once or multiple times as needed.

[0091] The dyeing process involves immersing a PVA-based resin film in a dyeing bath (iodine solution), which allows dichroic pigments such as iodine to be adsorbed and oriented on the PVA-based resin film. The iodine solution is typically an aqueous iodine solution containing iodine and an iodide as a dissolving agent. Examples of iodides include potassium iodide, lithium iodide, sodium iodide, zinc iodide, aluminum iodide, lead iodide, copper iodide, barium iodide, calcium iodide, tin iodide, and titanium iodide. From the viewpoint of controlling the potassium content in the polarization element, potassium iodide is suitable.

[0092] The concentration of iodine in the staining bath is preferably 0.01% by mass or more and 1% by mass or less, more preferably 0.02% by mass or more and 0.5% by mass or less. The concentration of iodide in the staining bath is preferably 0.01% by mass or more and 10% by mass or less, more preferably 0.05% by mass or more and 5% by mass or less, and even more preferably 0.1% by mass or more and 3% by mass or less.

[0093] The temperature of the dyeing bath is preferably 10°C or higher and 50°C or lower, more preferably 15°C or higher and 45°C or lower, and even more preferably 18°C ​​or higher and 30°C or lower. Since the degree of dyeing of the PVA-based resin film is affected by the temperature of the dyeing bath, the immersion time in the dyeing bath cannot be fixed. It is preferably 10 seconds or higher and 300 seconds or lower, more preferably 20 seconds or higher and 240 seconds or lower. The dyeing process can be performed only once or multiple times as needed.

[0094] The crosslinking process involves immersing a dyed PVA-based resin film in a treatment bath (crosslinking bath) containing a boron compound. The polyvinyl alcohol-based resin film is crosslinked by the boron compound, and iodine molecules or dye molecules can be adsorbed onto this crosslinked structure. Examples of boron compounds include boric acid, borates, and borax. The crosslinking bath is typically an aqueous solution, but it can also be a mixture of an organic solvent miscible with water and water. From the viewpoint of controlling the potassium content in the polarizing element, the crosslinking bath preferably contains potassium iodide.

[0095] In the crosslinking bath, the concentration of the boron compound is preferably 1% by mass or more and 15% by mass or less, more preferably 1.5% by mass or more and 10% by mass or less, and even more preferably 2% by mass or more and 5% by mass or less. When potassium iodide is used in the crosslinking bath, the concentration of potassium iodide in the crosslinking bath is preferably 1% by mass or more and 15% by mass or less, more preferably 1.5% by mass or more and 10% by mass or less, and even more preferably 2% by mass or more and 5% by mass or less.

[0096] The temperature of the crosslinking bath is preferably above 20°C and below 70°C, more preferably above 30°C and below 60°C. Since the degree of crosslinking of the PVA resin film is affected by the temperature of the crosslinking bath, the immersion time in the crosslinking bath cannot be fixed in general. It is preferably above 5 seconds and below 300 seconds, more preferably above 10 seconds and below 200 seconds.

[0097] The crosslinking process can be performed only once, or it can be performed multiple times as needed.

[0098] The stretching process is a procedure in which a PVA-based resin film is stretched to a specified ratio along at least one direction. Typically, the PVA-based resin film is uniaxially stretched along the conveying direction (length direction). There are no particular limitations on the stretching method; both wet stretching and dry stretching methods can be used. The stretching process can be performed once or multiple times as needed. The stretching process can be performed at any stage in the manufacturing of polarization elements.

[0099] The treatment bath (stretching bath) in the wet stretching process can typically be water or a mixture of water and an organic solvent miscible with water. From the viewpoint of controlling the potassium content in the polarizing element, the stretching bath preferably contains potassium iodide. When potassium iodide is used in the stretching bath, the concentration of potassium iodide in the stretching bath is preferably 1% by mass or more and 15% by mass or less, more preferably 2% by mass or more and 10% by mass or less, and even more preferably 3% by mass or more and 6% by mass or less. From the viewpoint of suppressing film breakage during stretching, the treatment bath (stretching bath) may contain a boron compound. When a boron compound is included, the concentration of the boron compound in the stretching bath is preferably 1% by mass or more and 15% by mass or less, more preferably 1.5% by mass or more and 10% by mass or less, and even more preferably 2% by mass or more and 5% by mass or less.

[0100] The temperature of the stretching bath is preferably 25–80°C, more preferably 40–80°C, further preferably 50–75°C, and particularly preferably 65–75°C. Since the degree of stretching of the PVA-based resin film is affected by the temperature of the stretching bath, the immersion time in the stretching bath cannot be fixed. It is preferably 10 seconds or more and 800 seconds or less, more preferably 30 seconds or more and 500 seconds or less. The stretching treatment in the wet stretching method can be performed together with any one or more of the following processes: swelling, dyeing, crosslinking, and cleaning.

[0101] Examples of dry stretching methods include inter-roll stretching, heated roll stretching, and compression stretching. It should be noted that dry stretching can be performed concurrently with the drying process.

[0102] The total stretch ratio (cumulative stretch ratio) applied to the polyvinyl alcohol-based resin film can be appropriately set according to the purpose, preferably 2 times or more and 7 times or less, more preferably 3 times or more and 6.8 times or less, and even more preferably 3.5 times or more and 6.5 times or less.

[0103] The cleaning process involves immersing the polyvinyl alcohol (PVA) resin film in a cleaning bath to remove foreign matter remaining on the surface of the PVA resin film. The cleaning bath typically uses a water-based medium such as water, distilled water, or pure water. Furthermore, from the viewpoint of controlling the potassium content in the polarization element, potassium iodide is preferably used in the cleaning bath. In this case, the concentration of potassium iodide in the cleaning bath is preferably 1% by mass or more and 10% by mass or less, more preferably 1.5% by mass or more and 4% by mass or less, and even more preferably 1.8% by mass or more and 3.8% by mass or less.

[0104] The temperature of the cleaning bath is preferably 5°C or higher and 50°C or lower, more preferably 10°C or higher and 40°C or lower, and even more preferably 15°C or higher and 30°C or lower. Since the degree of cleaning of the PVA resin film is affected by the temperature of the cleaning bath, the immersion time in the cleaning bath cannot be fixed. It is preferably 1 second or higher and 100 seconds or lower, more preferably 2 seconds or higher and 50 seconds or lower, and even more preferably 3 seconds or higher and 20 seconds or lower. The cleaning process can be performed only once or multiple times as needed.

[0105] Furthermore, a metal ion treatment step is preferably included in the above-described process, or as a step different from the above-described process. The metal ion treatment step is performed by impregnating the polyvinyl alcohol-based resin film in a solution containing a metal salt of a second metal ion. Through the metal ion treatment step, the polyvinyl alcohol-based resin film contains the second metal ion.

[0106] The second metal ion is not limited to any metal ion other than potassium ions, but is preferably an ion of a metal other than an alkali metal. In particular, from the viewpoint of adjusting the color and imparting durability, at least one metal ion from the group consisting of transition metals such as cobalt, nickel, zinc, chromium, aluminum, copper, manganese, and iron is preferred. Among these metal ions, zinc ions are preferred from the viewpoint of adjusting the color and imparting heat resistance. Examples of zinc salts include zinc chloride, zinc halides such as zinc iodide, zinc sulfate, and zinc acetate.

[0107] Metal salt solutions can be used in metal ion treatment processes. The following describes an immersion treatment in a zinc-containing solution, using a zinc salt aqueous solution as a representative example in the metal ion treatment process.

[0108] The concentration of zinc ions in the zinc salt aqueous solution is 0.1–10% by mass, preferably in the range of 0.3–7% by mass. Furthermore, it is preferable that the zinc salt solution readily impregnates with zinc ions when using an aqueous solution containing potassium and iodide ions, such as potassium iodide. The concentration of potassium iodide in the zinc salt solution is preferably set to 0.1–10% by mass, more preferably 0.2–5% by mass.

[0109] When performing immersion treatment in a zinc-containing solution, the temperature of the zinc salt solution is typically 15–85°C, preferably 25–70°C. The immersion time is typically 1–120 seconds, preferably 3–90 seconds. During immersion treatment in the zinc-containing solution, the zinc content in the polyvinyl alcohol (PVA) resin film is adjusted to fall within the aforementioned range by modifying the concentration of the zinc salt solution, the immersion temperature of the PVA resin film in the zinc salt solution, and the immersion time. There are no particular restrictions on when to perform the immersion treatment in the zinc-containing solution. Immersion treatment in the zinc-containing liquid can be performed alone, or the zinc salt can be co-present in a dyeing bath, crosslinking bath, or stretching bath, and performed simultaneously with at least one of the dyeing, crosslinking, or stretching processes.

[0110] The drying step is a step of drying the PVA-based resin film cleaned in the cleaning step to obtain a polarizing element. Drying is performed by any appropriate method, and examples thereof include natural drying, air-blow drying and heat drying.

[0111] Manufacturing method 2 can be carried out through the following steps: a step of applying a coating liquid containing PVA-based resin onto a base film, a step of uniaxially stretching the obtained laminated film, a step of dyeing the PVA-based resin layer of the uniaxially stretched laminated film with a dichroic dye to allow the dichroic dye to be adsorbed, thereby forming a polarizing element, a step of treating the film adsorbed with the dichroic dye with a boric acid aqueous solution, and a step of washing with water after the treatment with the boric acid aqueous solution. The base film for forming the polarizing element can also be used as a protective layer of the polarizing element. If necessary, the base film can be peeled off and removed from the polarizing element.

[0112] <Transparent Protective Film>

[0113] The transparent protective film (hereinafter, also simply referred to as "protective film") used in the present embodiment is bonded to at least one side of the polarizing element via an adhesive layer. The transparent protective film is bonded to one side or both sides of the polarizing element, and is preferably bonded to both sides.

[0114] The protective film can have other optical functions at the same time, and can also be formed into a laminated structure in which a plurality of layers are stacked. From the viewpoint of optical characteristics, the thickness of the protective film is preferably thin. However, if it is too thin, the strength decreases and the processability is poor. A suitable film thickness is 5 μm or more and 100 μm or less, preferably 10 μm or more and 80 μm or less, more preferably 15 μm or more and 70 μm or less.

[0115] For the protective film, films such as acylated cellulose-based films, films containing polycarbonate-based resins, films containing cycloolefin-based resins such as norbornene, (meth)acrylic polymer films, and polyester resin films such as polyethylene terephthalate can be used. When a protective film is bonded to both sides of a polarizing element using an aqueous adhesive such as a PVA adhesive, from the viewpoint of moisture permeability, at least one of the protective films is preferably any one of an acylated cellulose-based film or a (meth)acrylic polymer film, and an acylated cellulose film is preferred among these.

[0116] At least one protective film can have a phase difference function for purposes such as viewing angle compensation. In this case, the protective film itself may have the phase difference function, or may additionally have a phase difference layer, or may be a combination of the two. The film with the phase difference function can be directly bonded to the polarizing element via an adhesive, or can be configured to be bonded via an adhesive or binder through another protective film that is bonded to the polarizing element.

[0117] <Adhesive layer>

[0118] The adhesive layer used to attach the protective film to the polarizing element is formed by the following adhesive.

[0119] (Adhesive)

[0120] The adhesive contains a first compound, a second compound, and a third compound. The adhesive can be a water-based adhesive, a solvent-based adhesive, an active energy radiation-cured adhesive, etc., and is not limited thereto; a water-based adhesive is preferred, and it is more preferably to contain a PVA-based resin. By using an adhesive containing the first, second, and third compounds to form an adhesive layer for bonding a polarizing element to a protective film, the decrease in the transmittance of the polarizing plate under high-temperature environments can be suppressed. Furthermore, by using an adhesive containing the second and third compounds, an adhesive with a sufficiently long service life for production can be manufactured. The application of the adhesive of the present invention is not limited; it is suitable for use in optical elements, for example, for bonding polarizing elements to protective films.

[0121] The thickness of the adhesive coating can be set to any value, for example, in a way that allows for the formation of an adhesive layer with a desired thickness after curing or heating (drying). The thickness of the adhesive layer is preferably 0.01 μm or more and 7 μm or less, more preferably 0.01 μm or more and 5 μm or less, further preferably 0.01 μm or more and 2 μm or less, and most preferably 0.01 μm or more and 1 μm or less.

[0122] When the adhesive is an aqueous adhesive containing PVA-based resin, the content of the third compound relative to 100 parts by weight of the PVA-based resin is, for example, 0.01 parts by weight or more and 400 parts by weight or less, preferably 0.05 parts by weight or more and 50 parts by weight or less, and more preferably 0.1 parts by weight or more and 10 parts by weight or less. If it is less than 0.01 parts by weight, the improvement in service life may sometimes be insufficient, and the suppression of polyene formation in polarizing elements at high temperatures may sometimes be insufficient. On the other hand, if it exceeds 400 parts by weight, the third compound may sometimes precipitate after the polarizing plate is manufactured.

[0123] When the adhesive is an aqueous adhesive containing PVA-based resin, the content of the first compound is preferably 0.1 parts by mass or more and 400 parts by mass or less relative to 100 parts by mass of PVA-based resin, more preferably 1 part by mass or more and 200 parts by mass or less, and even more preferably 3 parts by mass or more and 100 parts by mass or less. If it is less than 0.1 parts by mass, the suppression effect on polyene formation of the polarizing element under high temperature conditions may be insufficient. On the other hand, if it is more than 400 parts by mass, the first compound may precipitate after the polarizing plate is manufactured, resulting in an increase in haze.

[0124] When the adhesive is an aqueous adhesive containing PVA-based resin, the content of the second compound is preferably 1 part by mass and 60 parts by mass or less relative to 100 parts by mass of the PVA-based resin, more preferably 1.5 parts by mass and 50 parts by mass or less, and even more preferably 2 parts by mass and 45 parts by mass or less. If it is less than 1 part by mass, the improvement in water resistance may sometimes be insufficient. On the other hand, if it is more than 60 parts by mass, the solution stability of the adhesive may sometimes decrease.

[0125] In the adhesive, the content of the second compound, dialdehyde, is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and even more preferably 10 parts by mass or less, relative to 1 part by mass of the urea compound as the first compound. The lower limit is not limited, for example, it is 0.03 parts by mass or more. By keeping the ratio of the urea compound to dialdehyde in the adhesive within the above-mentioned range, it is easy to achieve both the improved high-temperature durability effect brought by the urea compound and the improved adhesiveness effect brought by the dialdehyde. It can be understood that the improved adhesiveness effect brought by the dialdehyde can lead to an improved water resistance effect. When the dialdehyde content exceeds 20 parts by mass relative to 1 part by mass of the urea compound, the improved high-temperature durability effect brought by the urea compound may not be fully realized. The ratio of the urea compound to dialdehyde in the adhesive and the ratio of the urea compound to dialdehyde in the adhesive layer can be considered the same.

[0126] In the adhesive, the content of the dicarboxylic acid as the third compound is preferably 0.001 parts by mass or more and 100 parts by mass or less, more preferably 0.01 parts by mass or more and 80 parts by mass or less, relative to 1 part by mass of the dialdehyde as the second compound. If it is less than 0.001 parts by mass, the improvement in pot life may sometimes be insufficient. On the other hand, if it is more than 100 parts by mass, the third compound may sometimes precipitate out after the polarizing plate is manufactured.

[0127] Regarding the aforementioned adhesive, in the case of forming an adhesive layer for bonding a polarizing element to a protective film, the amount of these compounds contained in the adhesive can be appropriately adjusted depending on whether the polarizing element to be bonded contains the first compound, the second compound, and the third compound, or does not contain the first compound, the second compound, and the third compound.

[0128] In a configuration in which a transparent protective film is bonded to both sides of a polarizing element via an adhesive layer, the adhesive layer on both sides of the polarizing element may be a layer containing a first compound, a second compound, and a third compound on only one side, but preferably both sides of the adhesive layer contain the first compound, the second compound, and the third compound.

[0129] To address the requirement for thinner polarizing plates, a polarizing plate with a transparent protective film on only one side of the polarizing element has been developed. In this configuration, the transparent protective film is also laminated via an adhesive layer containing a first compound, a second compound, and a third compound. As a method for manufacturing such a polarizing plate with a transparent protective film on only one side of the polarizing element, a method is considered whereby a polarizing plate with transparent protective films adhered to both sides via adhesive layers is first manufactured, and then one side of the transparent protective film is peeled off. When using this manufacturing method, only one adhesive layer may contain the first compound, the second compound, and the third compound, but it is preferable that both adhesive layers contain the first compound, the second compound, and the third compound. When only one adhesive layer contains the first compound, the second compound, and the third compound, it is preferable that the adhesive layer on the unpeeled film side contains the first compound, the second compound, and the third compound.

[0130] (Water-based adhesive)

[0131] As a water-based adhesive, any suitable water-based adhesive can be used, but a water-based adhesive containing PVA-based resin (PVA-based adhesive) is preferred. From the viewpoint of adhesion, the average degree of polymerization of the PVA-based resin contained in the water-based adhesive is preferably 100 or more and 5500 or less, more preferably 1000 or more and 4500 or less. From the viewpoint of adhesion, the average degree of saponification is preferably 85 mol% or more and 100 mol% or less, more preferably 90 mol% or more and 100 mol% or less.

[0132] As the PVA-based resin contained in the water-based adhesive, a PVA-based resin containing acetyl groups is preferred because it exhibits excellent adhesion and durability between the PVA resin layer and the protective film. For example, an acetyl group-containing PVA-based resin can be obtained by reacting a PVA-based resin with a diene using any method. The degree of acetyl group modification in the acetyl group-containing PVA-based resin is typically 0.1 mol% or more, preferably 0.1 mol% or more and 20 mol% or less. The resin concentration of the water-based adhesive is preferably 0.1 wt% or more and 15 wt% or less, more preferably 0.5 wt% or more and 10 wt% or less.

[0133] Dialdehyde, as the second compound, can be used as a crosslinking agent. Water-based adhesives may also contain crosslinking agents other than the second compound. Known crosslinking agents can be used. Examples of crosslinking agents include water-soluble epoxy compounds and isocyanates.

[0134] When the PVA resin is an acetyl acetyl PVA resin, the crosslinking agent is preferably any one of glyoxylate or hydroxymethyl melamine, and more preferably any one of glyoxylate.

[0135] Aqueous adhesives may also contain organic solvents. From the viewpoint of being miscible with water, alcohols are preferred organic solvents, and methanol or ethanol is more preferred among alcohols. The concentration of methanol in the aqueous adhesive is preferably 10% by mass or more and 70% by mass or less, more preferably 15% by mass or more and 60% by mass or less, and even more preferably 20% by mass or more and 60% by mass or less. By keeping the methanol concentration at 10% by mass or more, it is easier to suppress the polyolefination of PVA-based resins under high-temperature conditions. In addition, by keeping the methanol content at 70% by mass or less, it is possible to suppress the deterioration of the color tone. Some urea derivatives have low solubility in water, but are sufficiently soluble in alcohols. In this case, it is also a preferred method to prepare an alcoholic solution of the urea compound by dissolving it in an alcohol, and then adding the alcoholic solution of the urea compound to an aqueous PVA solution to prepare the adhesive.

[0136] (Active energy radiation curing adhesive)

[0137] Reactive energy radiation-cured adhesives are adhesives that cure upon exposure to reactive energy radiation such as ultraviolet light. Examples include adhesives containing polymerizable compounds and photopolymerizable initiators, adhesives containing photoreactive resins, and adhesive resins containing photoreactive crosslinking agents. Examples of polymerizable compounds include photopolymerizable monomers such as photocurable epoxy monomers, photocurable acrylic monomers, and photocurable urethane monomers, as well as oligomers derived from these monomers. Examples of photopolymerizable initiators include compounds containing substances that generate reactive species such as neutral free radicals, anionic free radicals, and cationic free radicals upon exposure to reactive energy radiation such as ultraviolet light.

[0138] <Layer containing compound 1, compound 2 and compound 3>

[0139] The first, second, and third compounds are not limited to being contained in the adhesive layer as described above. From the viewpoint of improving the high-temperature durability of the polarizing plate, they may also be contained in other layers besides the adhesive layer. In a polarizing plate with a transparent protective film on only one side, from the viewpoint of improving physical strength, a curing layer may be laminated on the side of the polarizing element opposite to the transparent protective film. This curing layer may be a layer containing the first, second, and third compounds.

[0140] The thickness of the layer containing the first compound, the second compound, and the third compound is preferably 0.1 μm or more and 20 μm or less, more preferably 0.5 μm or more and 15 μm or less, and even more preferably 1 μm or more and 10 μm or less.

[0141] [Composition of an image display device]

[0142] The polarizing plate of this embodiment is used in various image display devices such as liquid crystal display devices and organic EL display devices. In image display devices, when an interlayer filling configuration is used, where both sides of the polarizing plate are in contact with a solid layer other than an air layer, specifically an adhesive layer, the transmittance tends to decrease at high temperatures. In image display devices using the polarizing plate of this embodiment, even with an interlayer filling configuration, the decrease in the transmittance of the polarizing plate at high temperatures can be suppressed. An example of an image display device is a configuration having an image display unit, a first adhesive layer laminated to the viewing-side surface of the image display unit, and a polarizing plate laminated to the viewing-side surface of the first adhesive layer. This image display device may further include a second adhesive layer laminated to the viewing-side surface of the polarizing plate and a transparent member laminated to the viewing-side surface of the second adhesive layer. In particular, the polarizing plate of this embodiment is suitable for image display devices where a transparent member is disposed on the viewing side of the image display device, the polarizing plate is bonded to the image display unit via a first adhesive layer, and the polarizing plate and the transparent member are bonded via a second adhesive layer, forming an interlayer filling configuration. In this specification, either or both of the first adhesive layer and the second adhesive layer are sometimes referred to simply as "adhesive layer". It should be noted that the component used for bonding the polarizing plate to the image display unit, and the component used for bonding the polarizing plate to the transparent component, is not limited to an adhesive layer and may also be an adhesive layer.

[0143] <Image Display Unit>

[0144] Examples of image display units include liquid crystal units (LCDs) and organic EL units (OLEDs). As a liquid crystal unit, one can use a reflective liquid crystal unit that utilizes external light, a transmissive liquid crystal unit that utilizes light from a light source such as a backlight, or a semi-transmissive / semi-reflective liquid crystal unit that utilizes both external light and light from a light source. When the liquid crystal unit utilizes light from a light source, the image display device (liquid crystal display device) also provides a polarizing plate on the side opposite to the viewing side of the image display unit (liquid crystal unit), and further provides a light source. The polarizing plate on the light source side is preferably bonded to the liquid crystal unit via a suitable adhesive layer. As for the driving method of the liquid crystal unit, any type can be used, such as VA mode, IPS mode, TN mode, STN mode, or π-type bending orientation.

[0145] As an organic EL unit, it is suitable to use units that form a light emitter (organic electroluminescent body) by sequentially stacking a transparent electrode, an organic light-emitting layer and a metal electrode on a transparent substrate.

[0146] Organic light-emitting layers are stacks of various organic thin films. For example, they can be stacks of hole injection layers containing triphenylamine derivatives and light-emitting layers containing fluorescent organic solids such as anthracene, stacks of these light-emitting layers and electron injection layers containing perylene derivatives, or stacks of hole injection layers, light-emitting layers and electron injection layers, etc.

[0147] <Attachment of image display unit to polarizing plate>

[0148] In the bonding of the image display unit and the polarizing plate, an adhesive layer (adhesive sheet) is suitable. From an operational perspective, it is preferable to bond the image display unit to the polarizing plate having an adhesive layer attached to one side of the polarizing plate. The attachment of the adhesive layer to the polarizing plate can be performed in a suitable manner. Examples include preparing an adhesive solution of 10% to 40% by mass, obtained by dissolving or dispersing a base polymer or its composition in a solvent containing a single substance or mixture of suitable solvents such as toluene or ethyl acetate, and directly attaching it to the polarizing plate using a suitable spreading method such as casting or coating; or forming the adhesive layer on a spacer and transferring it to the polarizing plate.

[0149] <Adhesive layer>

[0150] The adhesive layer can consist of one or more layers, preferably one layer. The adhesive layer can be composed of an adhesive composition with (meth)acrylic resin, rubber resin, urethane resin, ester resin, silicone resin, or polyvinyl ether resin as the main component. Among these, adhesive compositions using (meth)acrylic resin as the base polymer, which exhibits excellent transparency, weather resistance, and heat resistance, are suitable. The adhesive composition can be either an active energy radiation-cured or thermosetting type.

[0151] The (meth)acrylic resin (base polymer) used in the adhesive composition is preferably a polymer or copolymer with one or more of the following (meth)acrylate monomers: butyl (meth)acrylate, ethyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, etc. It is preferable to copolymerize the polar monomer with the base polymer. Examples of polar monomers include (meth)acrylic acid compounds, 2-hydroxypropyl (meth)acrylate compounds, hydroxyethyl (meth)acrylate compounds, (meth)acrylamide compounds, N,N-dimethylaminoethyl (meth)acrylate compounds, glycidyl (meth)acrylate compounds, etc., monomers having carboxyl, hydroxyl, amide, amino, epoxy, etc.

[0152] The adhesive composition may contain only the aforementioned base polymer, but typically also contains a crosslinking agent. Examples of crosslinking agents include metal ions with a valence of divalent or higher that form a carboxylic acid metal salt with a carboxyl group, polyamine compounds that form an amide bond with a carboxyl group, polyepoxide compounds or polyols that form an ester bond with a carboxyl group, and polyisocyanate compounds that form an amide bond with a carboxyl group. Among these, polyisocyanate compounds are preferred.

[0153] The active energy radiation-curing adhesive composition possesses the property of curing upon irradiation with active energy radiation such as ultraviolet rays or electron beams. It exhibits adhesiveness even before irradiation, enabling it to adhere tightly to substrates such as films, and its curing upon irradiation allows for adjustment of the adhesion strength. The active energy radiation-curing adhesive composition is preferably ultraviolet-curing. In addition to the base polymer and crosslinking agent, the active energy radiation-curing adhesive composition also contains an active energy radiation-polymerizable compound. Depending on the requirements, it may contain photopolymerization initiators, photosensitizers, etc.

[0154] The adhesive composition may contain additives such as microparticles, beads (resin beads, glass beads, etc.) for imparting light scattering properties, glass fibers, resins other than the base polymer, tackifiers, fillers (metal powders, other inorganic powders, etc.), antioxidants, ultraviolet absorbers, dyes, pigments, colorants, defoamers, corrosion inhibitors, and photopolymerization initiators.

[0155] The adhesive layer can be formed by applying an organic solvent dilution of the adhesive composition described above to the surface of a substrate film, image display unit, or polarizer and then drying it. The substrate film is typically a thermoplastic resin film; a typical example is a separator that has undergone a release treatment. The separator can be, for example, a film obtained by performing a release treatment, such as silicone treatment, on the surface of a film containing resins such as polyethylene terephthalate, polybutylene terephthalate, polycarbonate, or polyarylate, where the adhesive layer is formed.

[0156] An adhesive composition can be directly applied to the release surface of the diaphragm to form an adhesive layer, and this adhesive layer with the diaphragm is then laminated onto the surface of the polarizing plate. Alternatively, an adhesive composition can be directly applied to the surface of the polarizing plate to form an adhesive layer, and the diaphragm can be laminated onto the outer surface of the adhesive layer.

[0157] When the adhesive layer is applied to the surface of the polarizing plate, it is preferable to perform surface activation treatments such as plasma treatment or corona treatment on the bonding surface of the polarizing plate and / or the bonding surface of the adhesive layer, and more preferably to perform corona treatment.

[0158] In addition, an adhesive sheet may be prepared in which an adhesive layer is formed by applying an adhesive composition on a second separator, and another separator is laminated on the formed adhesive layer. The adhesive layer with separator, obtained by peeling the second separator off the adhesive sheet, is laminated on the polarizing plate. The second separator is a separator that has weaker adhesion to the adhesive layer than the above-mentioned separator and can be easily peeled off.

[0159] The thickness of the adhesive layer is not particularly limited. For example, it is preferably 1 µm or more and 100 µm or less, more preferably 3 µm or more and 50 µm or less, and may be 20 µm or more.

[0160] <Transparent Member>

[0161] Examples of the transparent member disposed on the viewing side of an image display device include a transparent plate (window layer), a touch panel, and the like. A transparent plate having appropriate mechanical strength and thickness can be used. Examples of such a transparent plate include transparent resin plates such as polyimide-based resins, acrylic resins, and polycarbonate-based resins, or glass plates. A functional layer such as an anti-reflection layer may be laminated on the viewing side of the transparent plate. In addition, when the transparent plate is a transparent resin plate, a hard coat layer can be laminated to improve physical strength, and a low moisture permeability layer can be laminated to reduce moisture permeability. As the touch panel, various touch panels such as a resistive film type, a capacitive type, an optical type, and an ultrasonic type, a glass plate having a touch sensor function, a transparent resin plate, and the like can be used. When a capacitive touch panel is used as the transparent member, it is preferable to provide a transparent plate formed of glass or transparent resin at a position closer to the viewing side than the touch panel.

[0162] <Bonding of Polarizing Plate and Transparent Member>

[0163] For bonding the polarizing plate and the transparent member, an adhesive or an active energy ray-curable adhesive is suitably used. When an adhesive is used, the adhesive can be provided by an appropriate method. Specific examples of the providing method include the providing method for the adhesive layer used in the bonding of the image display unit and the polarizing plate described above.

[0164] When an active energy ray-curable adhesive is used, in order to prevent the spread of the adhesive solution before curing, the following method is suitably used: a dam material is provided so as to surround the peripheral edge on the image display panel, the transparent member is placed on the dam material, and the adhesive solution is injected. After injecting the adhesive solution, after performing position alignment and degassing as needed, active energy rays are irradiated to cure the adhesive.

[0165] Examples

[0166] The present invention will now be described in detail based on specific embodiments. The materials, reagents, quantities, proportions, and operations shown in the following embodiments may be appropriately modified without departing from the spirit of the invention.

[0167] Therefore, the present invention is not limited to the following embodiments.

[0168] (1) Measurement of the thickness of the polarization element:

[0169] Measurements were performed using a digital micrometer "MH-15M" manufactured by Nikon Corporation.

[0170] (2) Measurement of the polarization degree of the polarizer with visibility correction, the transmittance of the visible-corrected monomer, and the hue:

[0171] Measurements were performed using a spectrophotometer with an integrating sphere (V7100 manufactured by Nippon Spectrophotometer Co., Ltd., 2-degree field of view; C light source).

[0172] (3) Determination of boron content:

[0173] Dissolve 0.2 g of the polarizing element in 200 g of a 1.9% (w / w) mannitol aqueous solution. Next, titrate the resulting aqueous solution with a 1 mol / L sodium hydroxide aqueous solution. Calculate the boron content of the polarizing element by comparing the amount of sodium hydroxide solution required for neutralization with a standard curve.

[0174] (4) Determination of zinc ion content:

[0175] Nitric acid was added to a precisely weighed polarization element, and acid decomposition was performed using a Milestone General microwave sample pretreatment device (ETHOSD). The resulting solution was used as the assay solution. The zinc ion content was quantified using an Agilent Technologies ICP-OES system (5110 ICP-OES) to determine the zinc concentration in the assay solution, calculated as the mass of zinc relative to the mass of the polarization element.

[0176] (5) Determination of boron adsorption rate of PVA-based resin membrane:

[0177] PVA-based resin membranes cut into 100 mm squares were immersed in pure water at 30°C for 60 seconds, and then immersed in an aqueous solution containing 5 parts boric acid at 60°C for 120 seconds. The PVA-based resin membranes removed from the boric acid aqueous solution were dried in an oven at 80°C for 11 minutes. After conditioning at 23°C and 55% RH for 24 hours, boron-containing PVA membranes were obtained. 0.2 g of the thus obtained boron-containing PVA-based resin membrane was dissolved in 200 g of a 1.9% (w / w) mannitol aqueous solution. Next, the resulting aqueous solution was titrated with a 1 mol / L sodium hydroxide aqueous solution. The boron content of the PVA-based resin membrane was calculated by comparing the amount of sodium hydroxide solution required for neutralization with a standard curve. The boron content of the thus obtained PVA-based resin membrane was used as the boron adsorption rate of the PVA-based resin membrane.

[0178] (Fabrication of polarization element 1)

[0179] A 30 μm thick polyvinyl alcohol (PVA) resin film with a boron adsorption rate of 5.71% by mass was immersed in pure water at 21.5 °C for 79 seconds (swelling treatment). Then, it was immersed in an aqueous solution containing 1.0 mM iodine at 23 °C for 151 seconds (dyeing process). Next, it was immersed in an aqueous solution containing 2.5 / 4 / 100 potassium iodide / boric acid / water at 68.5 °C for 76 seconds (first crosslinking process). Following this, it was immersed in an aqueous solution containing 3 / 5.5 / 0.6 / 100 potassium iodide / boric acid / zinc chloride / water at 45 °C for 11 seconds (second crosslinking process, metal ion treatment process). Finally, it was cleaned in a cleaning bath (cleaning process) and dried at 38 °C (drying process) to obtain a 12 μm thick polarizing element formed by iodine adsorption and orientation in PVA. The stretching was mainly carried out during the dyeing and first cross-linking processes, with a total stretching ratio of 5.85 times. The resulting polarizing element contained 0.17% zinc ions by mass and 4.62% boron by mass.

[0180] (Preparation of PVA solution for adhesives)

[0181] 50g of a modified PVA resin containing acetyl groups (manufactured by Mitsubishi Chemical Corporation: GOHSENX Z-410) was dissolved in 950g of pure water, heated at 90°C for 2 hours, and then cooled to room temperature to obtain a PVA solution for adhesives.

[0182] (Preparation of adhesives 1-3 for polarizing plates)

[0183] Adhesives 1-3 were prepared by combining PVA solution, urea, commercially available 40% glyoxal solution, maleic acid, and purified water, with the contents of PVA, urea, glyoxal, and maleic acid as shown in Table 1. It should be noted that the adhesives were used 3 days after preparation.

[0184] [Table 1]

[0185]

[0186] (Saponification of acylated cellulose membranes)

[0187] A commercially available acylated cellulose membrane TJ40UL (manufactured by Fujifilm Corporation: 40 μm thickness) was immersed in a 1.5 mol / L NaOH aqueous solution (saponification solution) maintained at 55°C for 2 minutes, followed by washing with water. Then, the membrane was immersed in a 0.05 mol / L sulfuric acid aqueous solution at 25°C for 30 seconds, and further washed under running water for 30 seconds to neutralize the membrane. This process was then repeated three times using an air knife to remove water. After water removal, the membrane was dried in a drying zone at 70°C for 15 seconds, thus producing a saponified membrane.

[0188] (Preparation of polarizing plates 1-3)

[0189] Using adhesive 1 prepared and stored for 3 days as described above, saponified acylated cellulose films were laminated onto both sides of polarizing element 1 using a roller laminator, and then dried at 80°C for 5 minutes to obtain polarizing plate 1. The adhesive layer was adjusted to a thickness of 50 nm on both sides after drying.

[0190] In the fabrication of polarizing plate 1, adhesive 1 was changed to adhesive 2-3, resulting in polarizing plate 2-3.

[0191] (Adjustment of moisture content in polarizing plate (polarizing element))

[0192] The polarizing plates 1-3 obtained above were stored for 72 hours at a temperature of 20°C and relative humidity of 30%, 35%, 40%, 45%, 50%, or 55%. The moisture content was measured using the Karl Fischer method at 66, 69, and 72 hours of storage. Under any humidity condition, the moisture content remained unchanged at 66, 69, and 72 hours of storage. Therefore, the moisture content of polarizing plates 1-3 can be considered to be the same as the equilibrium moisture content of the 72-hour storage environment used in this experimental example. When the moisture content of a polarizing plate reaches equilibrium in a certain storage environment, it can be assumed that the moisture content of the polarizing element in the polarizing plate also reaches equilibrium in that storage environment. Furthermore, when the moisture content of the polarizing element in a polarizing plate reaches equilibrium in a certain storage environment, it can be assumed that the moisture content of the polarizing plate also reaches equilibrium in that storage environment.

[0193] (Adjustment of moisture content of polarizing plates 1-3)

[0194] The polarizers 1 to 3 were stored at 20°C and 55% relative humidity for 72 hours to achieve an equilibrium moisture content of 55% relative humidity in an environment of 20°C. The moisture content of the polarizers 1 to 3 was then adjusted.

[0195] <High Temperature Durability Evaluation>

[0196] (Preparation of the evaluation sample)

[0197] For polarizing plates 1 to 3 with adjusted moisture content, an acrylic adhesive (manufactured by Lindeco Co., Ltd., product number: #7) is formed on both sides. The plates are then cut into 50mm × 100mm sizes with the absorption axis parallel to the long side. Alkali-free glass (manufactured by Corning Co., Ltd. "EAGLE XG") is then bonded to each adhesive surface to produce evaluation samples.

[0198] <Single-cell transmittance evaluation (105℃)>

[0199] At a temperature of 50℃ and a pressure of 5 kgf / cm 2 After autoclaving the evaluation samples of polarizers 1-3 for 1 hour (490.3 kPa), they were placed in an environment of 23°C and 55% relative humidity for 24 hours. Then, the transmittance (initial value) of the evaluation samples of polarizers 1-3 was measured. They were then stored in a heating environment of 105°C, and the transmittance was measured every 50 hours up to 100-200 hours. Evaluation was based on the time it took for the transmittance to decrease by more than 5% relative to the initial value. The results are shown in Table 2.

[0200] When the transmittance decreases to less than 5% after 200 hours: A

[0201] When the transmittance decreases by more than 5% within 150–200 hours: B

[0202] When the transmittance decreases by more than 5% within 100-150 hours: C

[0203] When the transmittance decreases by more than 5% after 100 hours: D

[0204] <Water Resistance Evaluation (Warm Water Immersion Test)>

[0205] The water resistance test in this embodiment was conducted according to the water resistance test described in Japanese Patent Application Publication No. 2009-025728

[0060] . An acrylic adhesive (manufactured by Lintec Corporation, product number: #7) was formed on one side of the polarizing plate prepared above. Furthermore, the plate was cut into strips of 50mm × 20mm with the absorption axis (tension direction) of the polarizing plate as the long side, and the dimensions along the long side were accurately measured. Here, the evaluation sample was shown to exhibit a unique color uniformly across the entire surface due to the iodine adsorbed on the polarizing element.

[0206] Holding the sample by its short side with a gripper, approximately 80% of its length was immersed in a water bath at 60°C for 4 hours. The sample was then removed from the water bath and the moisture was wiped off. Immersion in warm water causes the polarizing element of the polarizing plate to shrink. The degree of shrinkage of the polarizing element was evaluated in three stages according to the following criteria by measuring the distance from the center of the short side of the sample, from the end of the sample (the end of the protective film), to the end of the shrunken polarizing element. The results are shown in Table 2.

[0207] When the distance from the end of the sample to the end of the polarizing element is less than 1 mm: A

[0208] Case B: The distance from the end of the sample to the end of the polarizing element is more than 1 mm but less than 3 mm.

[0209] When the distance from the end of the sample to the end of the polarizing element is greater than 3 mm: C

[0210] [Table 2]

[0211]

[0212] It is evident that polarizing plates containing compounds 1 (urea), 2 (glyoxal), and 3 (maleic acid) in the adhesive exhibit superior high-temperature durability compared to polarizing plates without urea in the adhesive, even when exposed to a high temperature of 105°C, as their transmittance does not easily decrease. Furthermore, for any adhesive, even polarizing plates manufactured after a 3-day storage period demonstrate excellent water resistance, making them adhesives with a sufficiently long service life for productivity.

Claims

1. A polarizing plate having a polarizing element and a transparent protective film, said polarizing element being formed by adsorbing and oriented dichroic pigments onto a polyvinyl alcohol-based resin layer, said transparent protective film being laminated on at least one side of said polarizing element. The polarizing element and the transparent protective film are bonded together by an adhesive layer formed of an adhesive containing a first compound, a second compound, and a third compound. The first compound is selected from at least one of urea, urea derivatives, thiourea, and thiourea derivatives. The second compound is a dialdehyde. The third compound is a dicarboxylic acid. The adhesive comprises a polyvinyl alcohol-based resin. In the adhesive, relative to 100 parts by weight of the polyvinyl alcohol-based resin, the content of the first compound is 3 parts by weight or more and 100 parts by weight or less, the content of the second compound is 2 parts by weight or more and 45 parts by weight or less, and the content of the third compound is 0.1 parts by weight or more and 10 parts by weight or less. In the adhesive, the content of the second compound is 0.03 parts by mass or more and 20 parts by mass or less relative to 1 part by mass of the first compound.

2. The polarizing plate according to claim 1, wherein, The dialdehyde is glyoxal.

3. The polarizing plate according to claim 1 or 2, wherein, The thickness of the adhesive layer is greater than 0.01 μm and less than 7 μm.

4. The polarizing plate according to claim 1 or 2, wherein, The polarizing plate is used in an image display device. In the image display device, a solid layer is disposed in contact with both sides of the polarizing plate.

5. An image display device comprising an image display unit, a first adhesive layer laminated on the observation-side surface of the image display unit, and a polarizing plate laminated on the observation-side surface of the first adhesive layer, as described in any one of claims 1 to 4.

6. The image display device according to claim 5, further comprising a second adhesive layer laminated on the observation-side surface of the polarizing plate, and a transparent component laminated on the observation-side surface of the second adhesive layer.

7. The image display device according to claim 6, wherein, The transparent component is a glass plate or a transparent resin plate.

8. The image display device according to claim 6, wherein, The transparent component is a touch panel.

9. An adhesive comprising a first compound, a second compound, a third compound, and a polyvinyl alcohol-based resin, The first compound is selected from at least one of urea, urea derivatives, thiourea, and thiourea derivatives. The second compound is a dialdehyde. The third compound is a dicarboxylic acid. In the adhesive, relative to 100 parts by weight of the polyvinyl alcohol-based resin, the content of the first compound is 3 parts by weight or more and 100 parts by weight or less, the content of the second compound is 2 parts by weight or more and 45 parts by weight or less, and the content of the third compound is 0.1 parts by weight or more and 10 parts by weight or less. In the adhesive, the content of the second compound is 0.03 parts by mass or more and 20 parts by mass or less relative to 1 part by mass of the first compound.

Citation Information

Patent Citations

  • Liquid crystal panel support, electronic equipment having the same and manufacture of the same equipment

    JP1999174417A

  • Adhesive for polarizing plate, polarizing plate, its manufacturing method, optical film, and image display apparatus

    JP2005189615A

  • Polarizing plate and method of manufacturing the same

    JP2009025728A

  • Polarizing plate, method for producing the same and adhesive for polarizing plate production

    JP2010276673A

  • Polarizing plate and image display device, and manufacturing method of those

    JP2014102353A